Mental health is an integral component of public health in the modern world: the dynamics of the term use in scientific publications - O.L. Burak; N.B. Fedorkiv; I.M. Karpinets; R.Y. Kovalchuk; N.V. Chaplynska (Medičnì Perspektivi, 2025)
Mental health is a fundamental right of every person and an integral part of health. Its condition is influenced by socio-economic factors that need to be considered in comprehensive strategies for strengthening mental health, prevention of mental disorders, treatment and recovery using a whole-of-government approach. The purpose of our work was to study the dynamics of the term “mental health” use in publications available in electronic scientometric databases, in particular PubMed and Google Scholar, and to analyse such kind of works appearance after significant social events. To achieve the goal of the research we used key words “mental health”, “mental health natural disaster”, “mental health armed conflicts”, “mental health general practitioner” for scientific publications search in the scientometric medical database PubMed and key word “mental health” (in Ukrainian) in Google Scholar database. We analyzed the dynamics of publications from the moment of their first appearance until today in English and Ukrainian with search filters “systematic review” and “systematic review”. The package of statistical functions of Microsoft Excel for Microsoft 365 was used to analyse trends. For the term «mental health» in PubMed database we got more than five hundred thousand results, of which nineteen thousand publications were systematic reviews. Under the influence of natural disasters and military operations, the mental health of many people is deteriorating. In Ukraine due to military operations the entire population is at risk of mental health disorders which requires urgent responses of governmental and non-governmental organizations and creates additional challenges for public health. So, in the available scientific publications an annual increase in the number of publications by search query, “mental health” has been established. After significant social events (natural disasters, military conflicts), numerous publications highlighting the impact of the event on the mental health of the affected population appear.